Derivation of aquatic life criteria for four phthalate esters and their ecological risk assessment in Liao River. (April 2019) - Zheng, Xin; Yan, Zhenguang; Liu, Peiyuan; Li, Hong; Zhou, Junli; Wang, Yizhe; Fan, Juntao; Liu, Zhengtao
Abstract: As a critical family of endocrine disruptors, phthalate esters (PAEs) attracted considerable attentions due to increasingly detected worldwide. Aquatic life criteria (ALC) for PAEs are crucial for their accurate ecological risk assessment (ERA) and have seldom been derived before. Given this concern, the purpose of the present study is to optimize the ALCs of four priority PAEs to estimate their ecological risks in Liao River. Reproductive endpoint was found to be more sensitive than other endpoints. Thus, reproduction related toxicity data were screened to derive ALCs applying species sensitivity distribution (SSD) method. ALCs of DEHP, DBP, BBP and DEP were calculated to be 0.04, 0.62, 4.71 and 41.9 μg L −1, which indicated decreased toxicity in sequence. Then, the derived ALCs of the four PAEs were applied to estimate their ecological risks in Liao River. A total of 27 sampling sites were selected to detect and analyze the exposure concentrations of PAEs. ERA using the hazard quotient (HQ) method was conducted. The results demonstrated that DEHP exhibited higher risks at 92.6% of sampling sites, and risks posed by DBP were moderate at 63.0% sampling sites. However, risks posed by BBP were low at 70.4% of sampling sites, and there were no risks posed by DEP at 96.3% of sampling sites. The results of probabilistic ecological risk assessment (PERA) indicated that probabilities of exceeding effects thresholds on 5% of species were 60.41%, 0%, 0.12%, 14.28% for DEHP, DEP, BBP and DBP, respectively. The work provides useful information to protect aquatic species in Liao River. Graphical abstract: Image 1 Highlights: Untraditional toxicity endpoints were adopted to derive aquatic life criteria（ALCs） of four PAEs. ALCs for PAEs based on reproductive were far less than water quality standards of corresponding PAEs. Two approaches of ecological risk assessment were performed based on measured concentration of four PAEs in Liao River. The ecological risk of DEHP in Liao River should be paid attention.